2010
DOI: 10.1016/j.bcp.2010.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Increased responsiveness to JNK1/2 mediates the enhanced H2O2-induced stimulation of Cl−/HCO3− exchanger activity in immortalized renal proximal tubular epithelial cells from the SHR

Abstract: . Increased responsiveness to JNK1/2 mediates the enhanced HO-induced stimulation of Cl/HCO exchanger activity in immortalized renal proximal tubular epithelial cells from the SHR. Biochemical Pharmacology, Elsevier, 2010, 80 (6) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…Similar to that previously reported for H 2 O 2 [Simao et al, 2008a;Simao et al, 2010], in the present study SHR PTE cells were also found to have an enhanced sensitivity to DTDP-induce stimulation of Cl [Ying et al, 2007]. In the current study we also found that DTDP treatment increased the affinity of the transporter for HCO In the present study, a lower content of free thiol groups was detected, i.e., cysteine residues in the reduced form, in SHR than in WKY PTE cells.…”
Section: ããsupporting
confidence: 92%
See 4 more Smart Citations
“…Similar to that previously reported for H 2 O 2 [Simao et al, 2008a;Simao et al, 2010], in the present study SHR PTE cells were also found to have an enhanced sensitivity to DTDP-induce stimulation of Cl [Ying et al, 2007]. In the current study we also found that DTDP treatment increased the affinity of the transporter for HCO In the present study, a lower content of free thiol groups was detected, i.e., cysteine residues in the reduced form, in SHR than in WKY PTE cells.…”
Section: ããsupporting
confidence: 92%
“…In the current study we also found that DTDP treatment increased the affinity of the transporter for HCO In the present study, a lower content of free thiol groups was detected, i.e., cysteine residues in the reduced form, in SHR than in WKY PTE cells. This correlates well with previous data that SHR PTE cells have increased levels of H 2 O 2 production due to an imbalance between oxidant and antioxidant enzymes [Simao et al, 2008a;Simao et al, 2008b;Simao et al, 2010]. As a result, the thiol groups of proteins in SHR cells would be mostly in the oxidized form (and less in the ''free'' form).…”
Section: ããsupporting
confidence: 92%
See 3 more Smart Citations